MANAGING BRANDS’ POPULARITY ON FACEBOOK: POST TIME, CONTENT, AND BRAND COMMUNICATION STRATEGIES - Tri Hanifawati; Utan Sahiro Ritonga; Euis Evi Puspitasari (Faculty of Economics and Business, Universitas Gadjah Mada, 2019)
Introduction: A brand’s popularity on social media affects its customers’ purchasing intention and purchasing decision. Background Problem: A review of the literature shows that a brand’s popularity on social media has a secure connection with its content and the time information about it is posted; allegedly the brand’s interactions are also influential. Indicators of its popularity include the number of likes, shares, comments, and views for it. Novelty: Previous brand popularity studies were limited to the features of likes, comments, and shares as a function of the content and time, and OLS was commonly used. However, this study adds the views feature and the function of the administrator’s comments to complete the gap. GLS is used as the method of analysis. Research Method: Data are collected through the observation of six top international food and beverage products’ categories on the Facebook fan page. The data were analyzed using the Seemingly Unrelated Regression (SUR), and the Mann-Whitney and Kruskal-Wallis methods. Findings: The study’s findings shows that video and the day to post have a significant influence and increase the number of likes, shares, comments, and views. A caption only shows significance to increase the number of likes and shares. The hour has a significant effect on comments and shares. The time of posting indicates that posting on weekdays and during busy periods is more effective for increasing the popularity of brands. The administrator’s comments significantly influence the increase in the number of comments and views, while two-way communication is more significant for increasing a brand’s popularity. Conclusion: These findings provide a deeper insight to help managers to improve their brand’s popularity on social media by exploring how brands manage their fan pages.